Multikulturalisme dalam Wajah Situasi Kita Komedi Situasi: Antara Kesedarajatan dan Kesenjangan - YUTANTI, WIDYA (Komunikator, 2012)
Multiculturalism is one of the problems in modern society. Multiculturalism is not pragmatic political doctrine, but it is wisdom in managing cultural differences among people. Indonesia is an archipelago which consists of thousands of islands and hundreds of cultures. There are many crucial conflicts caused by cultural issues, such as ethnicity, religion, race, and other cross cultural issues. In this circumstance, people should be aware and accommodating to accept multicultural reality in a plural society. Television as modern mass media is not only expected to be informative and entertaining media, but also educational media. Through TV broadcast, television has a great social responsibility to explore multiculturalism campaign. TV itself has a variety of programs. Situation comedy is one of the comedy genres which are aired on the television which provides enjoyable entertainment. With humor, strong characters, settings and its smooth implicit message, situation comedy becomes a favorite entertainment program. Unfortunately, this show is not safe enough to be watched. Sometimes, it demonstrates extreme jokes. These jokes touch cultural issues and they make problems from cultural differences. In situation comedy, they taunt each other with extreme insults. The producer always creates unique selling points by creating a program that presents stereotypes. It is dangerous for multiculturalism education. Keywords: Multiculturalism, situation comedy, television, mass media